Perbandingan Peran Dewan Pengawas Syariah Pada Perbankan Syariah di Indonesia dan Brunei Darussalam - Damayanti, Elsa Resti; Januri, Fauzan; Jaenudin, Jaenudin (Muqaranah, 2023)
This study theoretically examines the role of the sharia board in supervising sharia banks, especially the responsibilities and authority of its members. Furthermore, this paper examines whether the proportion of responsibility and authority is balanced or not. This is achieved by comparing the role of the sharia council in Indonesia with the role of the sharia council in Brunei Darussalam. This research is qualitative research with a comparative approach model. From the results of the study it was stated that Countries in the Southeast Asia region adopt a centralized Sharia governance model. The comparison is based on criteria such as: appointment, qualifications, process flow, governance and legislation. There is no significant difference in the role of the sharia supervisory board in both Indonesia and Brunei. The biggest difference between the two countries lies in the presence and absence of a special sharia governance system for sharia financial institutions. It can be said that Brunei and Indonesia from the legal framework will continue to experience development towards a better direction. The most important thing is that whatever type of regulations are set by the central bank, financial institutions must be willing to follow them.